Taking into account the fluid compressibility at its unsteady flow in pressure pipelines of fire extinguishing systems - Яхно, Олег Михайлович; Стась, Сергій Васильович; Гнатів, Роман Маріянович (Eastern-European Journal of Enterprise Technologies, 2015)
The urgency of the research topic, caused by insufficiency of the existing theoretical models and methods for calculating unsteady fluid flows was substantiated. The effect of fluid compressibility on the average velocity at unsteady flow was investigated. The nonstationary problem of fluid flow in the pipeline, when the pressures that vary randomly in time are set on the pipe ends, was considered. Based on this approximate solution, the influence of fluid compressibility on the average flow velocity at that allows to clarify the hydrodynamic parameters of fire extinguishing systems was analyzed. A mathematical model for calculating the parameters of the pressure fluid flow in pipelines of fire extinguishing systems, taking into account the dissipative processes at the unsteady motion of a compressible fluid was developed. Pressure and velocity distribution laws at unsteady laminar and turbulent flows, which take into account the structural features of the considered flows and the impact of inertia forces were obtained. In turn, the clarifications given will help to optimize the calculation in the design of automatic fire extinguishing systems and improve the operational efficiency of the latter.